Changes in epinephrine dispensings and allergy hospitalisations in Sweden in the years following the removal of autoinjector co-payments - Ahlstedt, Staffan; Bergström, Anna; Nilsson, Lennart; Kivistö, Juho E; Protudjer, Jennifer L P (Frontiers in Allergy, 2024)
IntroductionTo understand any possible healthcare system benefits and changes of behavior for the patients with the change in prescription co-payment in Sweden we aimed to provide an update on the trends of EAI dispensings and hospitalizations for the Swedish paediatric population (ages 0–19 years), from 2018 to 2022, including by sex and geographic region.MethodsUsing publically-available, population-level aggregate data from Sweden's National Board of Health and Welfare, we extracted information on annual epinephrine (ATC C01CA24) dispensings per 1,000 inhabitants from 2018 to 2023, overall, as well as stratified by sex, age groups and geographic region; and on inpatient stays 2018–2022 (ICD-10 code T78), anaphylaxis and other allergic reactions, per 100,000 individuals. We compared these estimates to those for adults ages 18 + years, for whom prescription co-payments remained in place.ResultsEAI dispensings remained stable for children and adults across the study period, with the exception of statistically significant decreases amongst dispensings for children across all ages in 2021 (6.65/1,000) and 2022 (7.37/1,000), compared to 2018 (8.63/1,000) (each year p = 0.03 compared to 2018 dispensings). National EAI dispensings did not statistically significantly differ from 2018 (8.63/1,000) to 2023 (6.70/1,000) amongst children. EAI dispensings for children ages 5 + years consistently exceed dispensings for adults per 1,000 inhabitants; only children aged 0–4 years had proportionately fewer dispensings. Children ages 0–4 years tended to be hospitalised more often than older children, albeit these differences were not statistically significant (all p > 0.97).ConclusionSubsequent to the removal of out-of-pocket costs for EAI, dispensings did not increase for children, although more EAI were dispensed to children from age 5 years, compared to younger children. Allergy-related hospitalisations were highest amongst children ages 0–4, lower amongst children ages 5–14 years, and again higher amongst those ages 15–19 years.